2014
DOI: 10.1007/s10735-014-9586-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic role of SGTA in human breast carcinoma correlates with tumor cell proliferation

Abstract: Small glutamine-rich tetratricopeptide repeat-containing protein alpha (SGTA) was reported to be implicated in various cellular processes and involved in control of cell cycle regulation and transcription. It may play a critical role in oncogenesis. In this study, to investigate the potential roles of SGTA in breast cancer, expression patterns, interaction and the correlation with clinical/prognostic factors of SGTA and Ki-67 were examined among patients with breast cancer. Immunohistochemistry and Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Lung tissues were crushed in frozen state, and then extracted with protein lysis buffer containing 1 % NP-40, 20 mM Tris (pH 7.4), 137 mM NaCl, 10 % glycerol, and 1 mM phenylmethyl sulfonyl fluoride (Zhu et al 2014). Lysates were centrifuged at 14,0009g for 15 min at 4°C and total proteins were harvested.…”
Section: Protein Isolation and Western Blot Analysismentioning
confidence: 99%
“…Lung tissues were crushed in frozen state, and then extracted with protein lysis buffer containing 1 % NP-40, 20 mM Tris (pH 7.4), 137 mM NaCl, 10 % glycerol, and 1 mM phenylmethyl sulfonyl fluoride (Zhu et al 2014). Lysates were centrifuged at 14,0009g for 15 min at 4°C and total proteins were harvested.…”
Section: Protein Isolation and Western Blot Analysismentioning
confidence: 99%
“…These events suggest that the expression of SGTA is induced by the overexpression of chaperones in various cancers types, not only prostate cancer [e.g. , oesophageal squamous cell carcinoma and breast carcinoma] [31, 32]. Although upregulation of SGTA expression may not be related to hormonal signalling, overexpressed SGTA plays an important role as an inhibitor of AR signalling and confers the androgen-independent characteristics in prostate cancer [3].…”
Section: Discussionmentioning
confidence: 99%
“…Another disease linked to androgen signaling is breast cancer, one of the most common cancers among women. A 2014 study (Zhu et al, 2014) first examined the relationship between SGTA and breast cancer cells and found that SGTA was overexpressed in breast cancer cells compared to normal tissue. They also found a positive correlation between SGTA concentration and breast cancer cell proliferation following SGTA knockout experiments.…”
Section: The Role Of Sgta In Breast Cancermentioning
confidence: 99%
“…These results suggest that SGTA levels could be a potential indicator of breast cancer progression as concentration was found to increase at a higher histological grade. Additionally, SGTA was recognized as a potential prognosis indicator (Zhu et al, 2014). This leaves SGTA as an interesting potential treatment target for breast cancer and thus more research should be done into this relationship (Zhu et al, 2014).…”
Section: The Role Of Sgta In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation